1979
DOI: 10.1177/00220345790580100101
|View full text |Cite
|
Sign up to set email alerts
|

Human Gingival Lymphocytes. I. Methodology for the Isolation of Human Gingival Lymphocytes

Abstract: Various methodologies were examined for the isolation of inflammatory cells from diseased human gingiva. The best recovery of viable gingival lymphocytes (gMNC) was achieved by a method which combined initial collagenase digestion followed by gentle teasing with an 18-gauge needle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…An important finding was that the percentage of different cell types in the original tissue sample did not significantly differ from the counts in the cell suspension. Moreover, the data are generally consistent with the findings of Mackler et al (1979) who reported similar percentages for the cell composition of gingiva. The method described here did not select for any cell type nor for cells in the DNA synthesis phase of the cell cycle.…”
Section: Differential Ceil Countssupporting
confidence: 90%
See 2 more Smart Citations
“…An important finding was that the percentage of different cell types in the original tissue sample did not significantly differ from the counts in the cell suspension. Moreover, the data are generally consistent with the findings of Mackler et al (1979) who reported similar percentages for the cell composition of gingiva. The method described here did not select for any cell type nor for cells in the DNA synthesis phase of the cell cycle.…”
Section: Differential Ceil Countssupporting
confidence: 90%
“…Previous investigations on the release of cells from human gingiva have used samples of tissue in various stages of inflammation, including gingivitis (Daly et al 1983), periodontitis (Mackler et al 1979) and conservatively treated periodontitis (Sinden & Walker 1979, O'Neill, Woodson & Mackler 1982. Cell yields varied between 3.6 x 10' cells per 100 mg tissue (Mackler et al 1979) and up to 1x10'' nucleated cells per 100 mg (Sinden & Walker 1979, Daly, Clancy & Cripps 1983. In contrast, yields up to 3.4 X IO' cells per 100 mg of tissue were consistently obtained with our optimal digestion rnixture, which is considerably greater than those previously obtained.…”
Section: Discussion Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic and functional characterization of lymphocytes from periodontally diseased tissues has received attention (Seytnour, Powell & Aitken 1983, Seymour et al 1983). Mechanical and enzymatic procedures have been described for isolation of viable human gingival lymphocytes (Sinden & Walker 1979, Mackler et al 1979, Okada, Kida & Yamagami 1982. Recently, cells from chronically infiamed human gingiva were obtained by a combination of 90min incubation in a collagenase-containing medium, followed by mechanical disruption (Daly, Clancy & Cripps 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, interpretation is still diflicult in as much as the responsiveness of peripheral blood lymphocytes may not reflect that of the cells in the often localized lesions. Recognition of this fact has recently led to a number of studies designed to extract cells from periodontally diseased tissue (Mackler et al 1979, Sinden & Walker 1979, Ivanyi 1980, Daly, Clancy & Cripps 1983a, Daly, Cripps & Clancy 1983b. However, only one study has investigated the blastogenic response of these extracted cells (Ivanyi 1980).…”
Section: Introductionmentioning
confidence: 99%